PENGEMBANGAN MODUL TATA SURYA MENGGUNAKAN HURUF BRAILLE BERBASIS NILAI-NILAI AL-QURAN - Rosida, Oknisa Nur; Riswanto, Riswanto; Suseno, Nyoto; Harjati, Purwiro (Universitas Muhammadiyah Metro, 2021)
Abstract: This research is a development research or R&D (Research and Development) aims to solar system module with braille based on Al-Quran values. According to know the module developed is to eligibility criteria of the module and student response. This development research uses the ADDIE model consisting of five stages namely is nalysis, design, development, implementation, and evaluation. Validation result have been accured was shows the eligibility of the module level with the precentage of the material expert test is 94,75%, the watch module design is 95,4%, the braille module design is 98,75%, the Quran interpretation is 78,75%, and the student’s response is 92,59%, wich is the test results fall to into the category of “very feasible”. So, it can be concluded that the modules is very suitable for use in learning in class of visual impairment in Junior High School of Disability VIII. Keywords: Development of modulebraille, Al-Quran values, visually impaired